Synthesis and biological evaluation of hydroxamate isosteres of acidic cannabinoids - Amin, Hawraz Ibrahim M.; Ruiz-Pino, Francisco; Collado, Juan A.; Appendino, Giovanni; Tena-Sempere, Manuel; Munoz, Eduardo; Caprioglio, Diego (Frontiers in Natural Products, 2023)
Despite their early discovery, acidic cannabinoids were long overlooked in terms of bioactivity. Stability issues as well as a pharmacological focus on 9-THC and its biological profile combined to relegate the non-narcotic native form of phytocannabinoids in a sort of investigational limbo. Recent studies have disclosed an attractive bioactivity profile for specific acidic phytocannabinoids, but concerns on their limited stability have remained substantially unaddressed. To solve this issue, we have developed the hydroxamate derivatives of 8-tetrahydrocannabinolic acid-A (8-THCA-AH, 6) and cannabidiolic acid (CBDAH, 5) as novel acidic cannabinoid bioisosteres, and report here their synthesis, bioactivity profile against specific cannabinoid targets, as well as promising in vivo activity in a murine model of polycystic ovarian syndrome (PCOS) associated to obesity.